Chlamydia Trachomatis associated reactive arthritis: A urinary PCR based study - Megha Sharma; Susmita Sharma; Aman Sharma; Kusum Sharma (Wolters Kluwer Medknow Publications, 2020)
Background and Objective: Chlamydia trachomatis is increasingly being associated with reactive arthritis (ReA). The present study was undertaken to assess the role of C. trachomatis in patients with ReA since such data is lacking from the Indian population. Materials and Methods: PCR using specific primers for C. trachomatis was carried out from urine samples of 65 patients with ReA, 20 of other inflammatory arthritis, and 20 healthy controls. Results: C. trachomatis DNA was detected from urinary samples with PCR in 24 (36%) of 65 ReA patients. PCR was negative in the patients of other inflammatory arthritis as well as in normal healthy control group. Out of the 24 patients with urinary PCR positivity, 14 (58.33%) were males and 10 (41.66%) were females. Conclusion: Urinary PCR plays an important role in rapid diagnosis of ReA associated with C. trachomatis.